Feasibility, Stability, and Multiple Research Joint Ventures. (6th March 2014) - Yao, Zhiyong; Zheng, Bingyong
Abstract We study multiple research joint ventures (RJVs) using a repeated game with imperfect monitoring. Compared with the single joint venture case, we show that cooperation in multiple joint ventures creates two advantages for participating firms. First, by linking decisions together across all joint ventures firms can mitigate the likelihood of cooperation breakdowns following bad R&D outcomes. Second, as the incentive cost to sustain cooperation is independent of the number of joint ventures, the economy of scale effect reduces the efficiency loss due to imperfect monitoring.